A need for a health IT portal to disseminate information about national health programmes in India. (4th November 2013) - Nanda, Anjali; Grover, Ashoo; Joshi, Ashish
The objective of our study is to evaluate information about the national health programmes in India, available over the internet and to study the challenges faced while acquiring this information. To achieve our objective, we used the key words national health programmes OR public health programmes OR health programs AND India in Google from January 1–January 10 2012, to find information about the existing health programmes. We chose first 20 web links across all the three search terms to yield 60 websites, which were then reviewed for their relevance. Only 16 websites were found to be relevant that met the inclusion criteria. The study showed that there was inadequate information about the existing national health programmes in India. This suggests a need to develop a national public health IT portal that can disseminate information about the various health programmes in a more structured manner and which is tailored to the needs of diverse group of stakeholders.